HUBUNGAN MOTIVASI BEROBAT GIGI DENGAN PENGALAMAN KARIES GIGI PADA PENGUNJUNG POLI GIGI DI PUSKESMAS BANJARBARU SELATAN - lawati, kartini; Kisworo Utami, Naning; Bunga Nurwati; Amperawati, Metty (Poltekkes Kemenkes Banjarmasin, 2024)
Dental and oral health for Indonesian people is still important and needs serious attention from health professionals, both doctors and dental nurses. According to the reports of data obtained at Puskesmas Banjarbaru South many patients have been visited with cases suffering from tooth pain or tooth decay. The study aims to find out the relationship between dental motivation and caries experience in dental poly visitors in Puskesmas Banjarbaru South. This type of research is analytically descriptive with a cross-sectional approach design. The total population in the study was 157 with a sample of 40 respondents taken using purposive sampling techniques. This study was tested using the Chi-Square test calculation. The results of the study obtained mostly dental motivation in the Puskesmas Banjarbaru South category low and experience caries category high, with the use of Chi-square testing obtaining p-value result 0,000 < α = 0.05 Ha accepted and Ho rejected. The conclusion of this study is that there is a link between the motivation of dental therapy and the experience of dental caries in dental poly visitors in Puskesmas Banjarbaru South. It is hoped to be able to increase the motivation of dentistry in visiting the puskesmas and examining the health of his teeth and mouth to maintain dental and oral health